The relations of social support and well-being in mothers of children with special needs during the covıd-19 pandemic: The mediating role of caregiving burden - Koç, Muharrem; Avci, Özlem Haskan; Elkaan, Gülşah; Kocadayi, Sinem; Erbiçer, Eyüp Sabir; Zencir, Tolga (Turkish Psychological Counseling and Guidance Association, 2024)
This study explores the relationship between social support and well-being in mothers of children with special needs during the COVID-19 pandemic with a specific focus on the mediating role of caregiving burden. The research investigates the challenges faced by families with special needs children, particularly mothers, due to the pandemic-related closure of schools and rehabilitation centers. The closure has intensified the caregiving burden on mothers, requiring full-time support for their children at home. Existing literature suggests a significant impact on the psychological well-being of families with special needs children, emphasizing the need for attention to this vulnerable group during the pandemic. The study formulates hypotheses related to the negative correlation between family support and caregiving burden, the negative correlation between caregiving burden and psychological well-being, and the positive correlation between family support and psychological well-being. Additionally, it hypothesizes that caregiving burden mediates the relationship between family support and psychological well-being. Using a relational research approach, the study employs a quantitative method to analyze data collected from 321 participants. The demographic information of the participants, including age, working condition, marital status, and the type of disability of their children, is presented. Data collection instruments include a Sociodemographic Information Form, Family Support Scale, Caregiving Burden Scale, and Psychological Well-being Scale. Results indicated a positive relationship between family support and psychological well-being, as well as a negative relationship between caregiving burden and psychological well-being. The mediation analysis confirmed that caregiving burden significantly partially mediates the relationship between family support and psychological well-being. The findings highlighted the crucial role of family support in enhancing the psychological well-being of mothers with special needs children. Additionally, the study emphasized the negative impact of increased caregiving burden on psychological well-being. These results contribute to the understanding of the challenges faced by families with special needs children during the COVID-19 pandemic and underscore the importance of targeted interventions to support this vulnerable group. Future research may explore strategies to involve fathers in the caregiving process and further enhance maternal mental health. © 2024 Turkish Psychological Counseling and Guidance Association. All rights reserved.
Keywords: Caregiving Burden; COVID-19 Pandemic; Family Counseling; Social Support; Special Needs